The use of a regularized heat-kernel expansion on supersymmetric and/or gauge invariant field theories - Abdalla, E.; Abdalla, M. C.B. (Elsevier, 1985)
We regularize (superfield) Green functions using a cut-off in the proper time integration of the heat-kernel expansion. Counterterms are easily computed using the background field method, up to two-loop order. Supersymmetry is explicitly maintained through use of supergraphs. The supermultiplet structure of the superconformal anomaly is easily obtained. © 1985.